‘The Dream of the Unified Field’: Originality, Influence, the Idea of a National Literature and Contemporary American Poetry - Ruediger Heinze (European Journal of American Studies)
This paper collates two critical ideas about American poetry: originality and influence. Under the precept of the former, poets and critics call for – and on occasion celebrate – an originally American, more or less coherent national poetry, while the latter hosts complaints about the “forfeiture of grand opportunities” (Shaw) exactly because contemporary American poetry fails to contribute to a genuinely innovative national literature. This failure is argued to be the result of an inability of poets to free themselves from incapacitating literary influences due to the “academization” and “inbred professionalism” (Altieri) of the creative writing programs. Both ideas, this essay will argue, although apparently oppositional, are based on the same – inherently inconsistent – notion of influence and predominantly appear in the context of discussions around the project/idea of a national poetry/literature. The paper will examine the critical history of these two ideas and their connection to the conception of an American national poetry.